Migraine Headache in Middle-Age and Late-Life Brain Infarcts: The Age Gene/Environment Susceptibility - Reykjavik Study - Scher, Ann I (2009)
CONTEXT: Migraine is considered to be an episodic condition with no long-term consequences. However, recent studies suggest that migraine attacks may be associated with pathologic changes in the brain, particularly in the cerebellum. OBJECTIVE: To determine whether, compared to those not reporting symptoms, individuals reporting migraine symptoms in mid-life, particularly aura, are at increased risk of late-life infarct-like lesions (hereafter referred to as infarcts). DESIGN: A population based cohort of men and women (b 1907-35) followed since 1967, answered questions about migraine symptoms in mid-life (mean age 51, range 33–65), more than 26 years prior to a late-life exam when brain MRI was acquired. Those reporting headaches once or more per month were asked about migraine symptoms, including nausea, unilateral location, photophobia, visual disturbance, and numbness. We classified headache sufferers as having migraine without aura (MO), migraine with aura (MA), or non-migraine headache. A comprehensive cardiovascular risk assessment was performed at both examinations. SETTING: Population-based study in Reykjavik, Iceland PARTICIPANTS: Men and women (n=4689, 57% women). MAIN OUTCOME MEASURE: Presence of infarcts – total and specifically located in the cortical, sub-cortical, and cerebellar regions. RESULTS: After adjusting for age, sex, and follow-up time, compared to those not reporting headaches once or more per month (n=3243), those with mid-life MA (n=361) had an increased risk of late-life infarcts (adjusted OR, 1.4; 95% confidence interval [CI], 1.1–1.8) that specifically reflected an association with cerebellar lesions in women (Women: 23.0% vs. 14.5%, adjusted OR 1.9; 95% CI 1.4–2.6 vs. Men 19.3% vs. 21.3%, adjusted OR, 1.0; 95% CI 0.6–1.8, p<0.04 for interaction by sex). There was no increased risk associated with mid-life MO or non-migraine headache or for other brain regions. CONCLUSIONS: Migraine with aura in mid-life was associated with late-life prevalence of cerebellar infarcts on MRI. This association was statistically significant only for women. This is consistent with the hypothesis that MA in mid-life is associated with late-life vascular disease that appears to be specific for the cerebellum and in women.